Effect of a family-centered empowerment model-based educational intervention on quality of life in women with endometriosis: a randomized controlled trial - Narges Abdollahi Senu; Maryam Armaghan; Hamidreza Zendehtalab; Vahid Ghavami; Kobra Mirzakhani (BMC Women's Health, 2026)
Abstract Background Endometriosis substantially impairs disease-specific quality of life across physical, psychological, and social domains, yet evidence regarding family-centered empowerment interventions remains limited. This study evaluated the effect of a family-centered empowerment model-based intervention on patient-reported quality-of-life outcomes measured using the Endometriosis Health Profile-30 (EHP-30) in women with endometriosis. Methods A randomized controlled trial was conducted on 64 women with clinically and ultrasonographically confirmed endometriosis referred to a specialized clinic in Mashhad, Iran. Participants were randomly assigned to an intervention group ( n = 32) receiving a 12-week family-centered empowerment program or a control group ( n = 32) receiving routine care. The primary outcome was endometriosis-specific quality of life measured using the five core EHP-30 domains (Pain, Control and Powerlessness, Emotional Well-being, Social Support, and Self-image), assessed at baseline and 12 weeks after baseline. Data were analyzed using analysis of covariance (ANCOVA) adjusted for baseline scores, with Bonferroni correction for multiple comparisons ( p < 0.01). Results Baseline characteristics were comparable between groups (all p > 0.05). After the intervention, ANCOVA revealed significant improvements in the intervention group across all five EHP-30 domains, all of which remained statistically significant after Bonferroni correction for multiple comparisons: Pain (adjusted mean difference: −8.87, 95% CI: −13.02 to − 4.72, p < 0.001, partial η² = 0.22), Control and Powerlessness (− 5.36, 95% CI: −7.41 to − 3.31, p < 0.001, partial η² = 0.31), Emotional Well-being (− 6.71, 95% CI: −9.38 to − 4.04, p < 0.001, partial η² = 0.29), Social Support (− 4.79, 95% CI: −6.93 to − 2.65, p < 0.001, partial η² = 0.25), and Self-image (− 2.70, 95% CI: −3.93 to − 1.47, p < 0.001, partial η² = 0.22). The largest effect sizes were observed in the Control and Powerlessness and Emotional Well-being domains. Conclusion Family-centered empowerment-based education was associated with improved patient-reported endometriosis-specific quality of life across all five EHP-30 domains compared with routine care. These findings support further evaluation of this intervention in larger multicenter trials with longer follow-up to determine the durability, clinical relevance, and generalizability of the observed benefits. Trial registration Iranian Registry of Clinical Trials, IRCT20220720055505N1. Registered on 31 July 2022.